Crossing the Gap: Older Adults Do Not Create Less Challenging Stepping Stone Configurations Than Young Adults - Jeschke, Amy M.; de Lange, Annemieke M. M.; Withagen, Rob; Caljouw, Simone R. (Frontiers in Psychology, 2020)
Background. Despite the known health benefits of physical activity, the number of older adults exercising regularly remains low in many countries. There is a demand for public open space interventions that can safely train balance, muscular strength, and cardiovascular fitness. In this participatory design study, older adults and young adults were to create their own stepping stones configurations. We provided them with six stepping stones, and examined the gap widths that each group of participants created and how they used the configurations. Results. The created absolute gap distances by the older adults were smaller than those of the younger adults. Yet the amount of challenge (in terms of the created gap widths relative to a person’s estimated stepping capability) did not significantly differ between the young and older adults. Furthermore, both groups created unstandardized stepping stone configurations in which the number of different gap widths did not significantly differ between the young and older adults. Interestingly, while using their personalized design over a given timespan, older adults made significantly more gap crossings than younger adults. This finding tentatively suggests that personalized design invites physical activity in older adults. Conclusions. The present study demonstrated that older adults are not more conservative in designing their own stepping stone configuration than young adults. Especially in light of the public health concern to increase physical activity in seniors, this is a promising outcome. However, field tests are needed to establish whether the older adults’ stepping stones designs also invite physical activity in their daily environment.